Moral entanglements the ancillary-care obligations of medical researchers - Richardson, Henry S. (New York ; Oxford : Oxford University Press, 2013)
Richardson's book is a defense of a position on a neglected topic in medical research ethics. Richardson points out that ethical regulations do not address one of the key dilemmas faced by medical researchers - whether or not they have obligations towards subjects who need care not directly related to the purpose of the study.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Keywords: Medical research personnel -- Professional ethics; Human experimentation in medicine -- Moral and ethical aspects; Biology -- Research -- Moral and ethical aspects; Health care rationing -- Moral and ethical aspects